A Historical Analysis of Randomized Controlled Trials in Anterior Cruciate Ligament Surgery. (20th December 2017) - Kay, Jeffrey; Memon, Muzammil; SA, Darren de; Simunovic, Nicole; Musahl, Volker; Fu, Freddie H.; Karlsson, Jon; Ayeni, Olufemi R.
Abstract : Background: The purpose of this systematic review was to comprehensively assess the quality of reporting of randomized controlled trials (RCTs) relating to anterior cruciate ligament (ACL) reconstruction. Specifically, this review explored factors related to the quality of the RCTs and trends in the quality of reporting over time. Methods: The online databases PubMed, Ovid (MEDLINE), and Embase were used to search for all RCTs on the topic of ACL reconstruction from database inception until April 14, 2016. The quality of reporting was evaluated using the Detsky quality index and the Consolidated Standards of Reporting Trials (CONSORT) checklist for reporting trials of nonpharmacologic treatments. A multivariate regression analysis was used to assess predictors of quality reporting. Results: The online search yielded 2, 933 articles, 412 of which met the inclusion criteria and were assessed for quality of reporting. There was a significant (p < 0.0001) increase in the number of RCTs published over time. The mean Detsky score (and standard deviation) across all included RCTs was 68.9% ± 13.2%. The strongest predictors of quality reporting were the inclusion of a CONSORT flow diagram (β-coefficient, 10.0; 95% confidence interval [CI]: 8.45 to 11.61; p < 0.0001) and being published in the year 2009 or later (β-coefficient, 5.2; 95% CI: 3.87 to 6.45; p < 0.0001). The factors demonstrating the greatest improvement over time were the inclusion of a full description of the randomization procedure (p = 0.001) and prospective calculation of the sample size (p = 0.002). Conclusions: There has been a significant increase in both the quantity and quality of RCTs relating to ACL reconstruction over time. Specifically, the reporting of a methodologically sound randomization process and prospective calculation of sample size have significantly improved in recent years. However, since the year 2009, the number of trials and reporting in these trials has remained relatively consistent. The use of a CONSORT flow diagram is a strong predictor of high-quality reporting.